Kriegsliteratur aus der DDR und die Zensur in der Volksrepublik Polen in den ersten Nachkriegsjahren - Rajch, Marek (Studia Germanica Posnaniensia, 2017)
From all of the German literature distributed in Poland during the first half of the nineteen fifties, that of the GDR was the most strongly represented, because like the People's Republic, it was part of the Eastern Bloc. A substantial part of this literature touched upon the themes of the Second World War. As some prominent Eastern German authors had taken part in the Spanish Civil War in 1936-1939, this subject also couldn't be ignored. The introduction in 1949 of socialist realism as the most important criterion of art, and particulary strong political pressure, led to a great deal of confusion and insecurity, not only for Polish publishing houses, but also among the censors, whose task was to take decisions about what literature could be printed. Censors’ opinions in this period often differed, not only in terms of detailed matter, but also in the final decisions about the eventual fate of the title submitted for evaluation.